(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: The field of heart transplantation has seen substantial progress in the last 40 years. The breakthroughs in long-term survival were followed by a period of stagnation in the last decade. This review summarises current recommendations for the identification of candidates for heart transplantation and their immunological and non-immunological postoperative follow-up. RESULTS: The progress made in the treatment of patients with advanced heart failure has considerably changed the profile of candidates for heart transplantation. Patients are older, and the load of co-morbidities is more important requiring careful evaluation for candidacy. Long-standing research in the field of immunosuppression made available various drugs, which decrease the risk of acute allograft rejection and prolong survival after heart transplantation. Powerful new molecules are entering early phase clinical studies, suggesting further improvement in the near future. As a consequence, treatment of non-immunological co-morbidity after heart transplantation will gain in importance, however, the base of evidence guiding current recommendations is poor. CONCLUSIONS: The substantial progress in heart failure treatment and immunosuppression after heart transplantation has changed the profile of heart transplant recipients. The arrival of new molecules will provide additional alternatives for immunosuppressive treatment while studies have to address non-immunological treatment in order to improve long-term survival after heart transplantation.